Peran Partisipasi Masyarakat dalam Pelaksanaan Pembangunan Infrastruktur di Kelurahan Dembe Jaya - Monika Sokoy; Yanti Aneta; Yacob Noho Nani (Transbahasa, 2025)
This study aims to determine the role of community participation in the implementation of infrastructure development in Dembe Jaya Village and the factors that influence it. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The research informants consisted of village officials and the community of Dembe Jaya Village. The results of the study indicate that community participation in infrastructure development in Dembe Jaya Village is reflected in four aspects, namely: (1) providing responses to development information; (2) involvement in planning through the Musrenbang forum; (3) participation in the implementation of physical and non-physical projects, although still dominated by certain groups; and (4) participation in utilizing and maintaining development results such as paving block roads and water channels. However, participation is not evenly distributed and is influenced by various factors. Factors that influence the level of community participation consist of internal factors such as awareness and level of understanding of residents, as well as external factors such as social conditions, mutual cooperation culture, economic limitations, and lack of effective public communication. Some residents are only active if there are incentives, and the involvement of certain groups such as immigrant communities is still relatively low. Therefore, a more inclusive, transparent and adaptive approach is needed to increase sustainable participation in development.